2017
DOI: 10.5430/jnep.v7n10p64
|View full text |Cite
|
Sign up to set email alerts
|

The influencing factors of absenteeism among nursing students

Abstract: The absence of nursing students from classrooms and clinical has a negative impact on their performance and prolongs the length of their studying. The aim of this study is to identify the influencing factors of absenteeism among nursing students at Minia University. This study was conducted at the Faculty of Nursing at Minia University, and Minia University Hospitals. The sample of students that participated in the study represented all academic levels as follows: first level 49/370, second level 49/292, third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…In the findings in this study on work overload as a reason for student absence, 89.4% of the respondents agreed. This corresponds with the finding by Abdelrahman and Abdelkade (2017:67) that one of the reasons why students were absent in the clinical areas was work overload. In the study by Mothobi (2017:82), students indicated that staff members were inhuman towards them, thus encouraging absenteeism.…”
Section: Discussion Of Resultssupporting
confidence: 90%
“…In the findings in this study on work overload as a reason for student absence, 89.4% of the respondents agreed. This corresponds with the finding by Abdelrahman and Abdelkade (2017:67) that one of the reasons why students were absent in the clinical areas was work overload. In the study by Mothobi (2017:82), students indicated that staff members were inhuman towards them, thus encouraging absenteeism.…”
Section: Discussion Of Resultssupporting
confidence: 90%
“…In the present study too, the teaching method was considered as the main reason for missing classes due to generational preferences and was further reviewed. Abdelrahman and Abdelkader[ 8 ] showed that nursing students too attributed the main reasons for their absenteeism to educational factors, including a lack of staff in the clinical field and a lack of understanding of the lecture's content. The present study considered another factor to be more critical by considering the empowerment of the professors.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] For example, nursing students’ absenteeism from classes adversely affects their performance and prolongs their duration of the study. [ 8 ] Absenteeism also prevents them from accessing relevant information and contact with relevant materials (clinical skills, lectures, and practical sessions) necessary for active learning. [ 9 ] Medical physiology education also states that classroom lectures should be considered an essential component.…”
Section: Introductionmentioning
confidence: 99%
“…It reduces the phobia of carrying out procedures on humans as they practice hands-on-patients as against the models used in nursing laboratories. However, regular attendance to work has been a challenge despite an expected percentage of attendance set by most training institutions (Abdelrahman & Abdelkader, 2017;Nawaz, Hussain, Sarwar, Afzal, Gilani, 2018). Chukwu et al (2017) argue that student nurse attendance during training is mandatory because it is a crucial requisite in the training and influences the learning outcomes and professionalism.…”
Section: Attendance To Workmentioning
confidence: 99%